Flipped Classrooms using Social Networks: An investigation on learning styles - Gunawardena, K.S.L; Liyanage, M.P.P (IEEE, 2018)
The Flipped Classroom concept has recently been trending as a novel approach to adding a refreshing touch to the traditional classroom lecture. Social Networks are increasingly becoming a ubiquitous characteristic of many learners and is often compared to a complementing platform to the more established learning management systems. In most conventional setups, learners have a diverse set of characteristics. One such - Learning styles, is often considered as necessary for ensuring productivity and learner satisfaction in a learning environment. This paper investigates learning styles used in a flipped classroom environment implemented with the aid of a popular social network. In the preliminary analysis, the learning styles of the learners are gathered through a computer-based test, and a simple feedback survey was carried out to evaluate whether the content presentation and flipped approach was satisfactory. The results in this case suggest that the satisfaction of students in a flipped classroom benefit from content prepared to match the selected learning styles of users (Visual).
Keywords: Flipped Classrooms; Learning Styles; Blended Learning; ICT in Education.